Odpowiedzi

Najlepsza Odpowiedź!
2009-10-14T18:06:28+02:00
14m²t-35mt-28mt²
u=------------------------
7mt

7mt(2m-5-4t)
=..............
7mt

u=2m-5-4t



9m²t²-21m²t
v=---------------------
3m²t


3m²t(3t-7)
=............
3m²t

v=3t-7

m²t²+0.5mt³
w=-----------------------=
-2mt²

mt²(m+1/2t)
=...............
-2mt²


w=-1/2m-1/4


u+v+w=2m-5-4t+3t-7-1/2m-1/4=1i1/2m-t-12 i1/4
9 3 9
  • Użytkownik Zadane
2009-10-14T18:14:18+02:00
14m²t-35mt-28mt²
u------------------------
7mt

9m²t²-21m²t
v=---------------------
3m²t

m²t²+0.5mt³
w=-----------------------
-2mt²


u+v+w=
(14m²t-35mt-28mt²) (9m²t²-21m²t ) (m²t²+0.5mt³)
------------------------ + ------------------ + ------------------=
(7mt ) (3m²t) (2mt²)

(3m²t)(2mt²)(14m²t-35mt-28mt²)+(7mt )(2mt²)(9m²t²-21m²t )+
--------------------------------------------------------------------------------
(7mt ) (3m²t) (2mt²)


+(7mt )(3m²t)(m²t²+0.5mt³)
---------------------------------------=
(7mt ) (3m²t) (2mt²)

(6m³t³)(14m²t-35mt-28mt²)+(14m²t³)(9m²t²-21m²t )+(21m³t²)(m²t²+0.5mt³)
--------------------------------------------------------------------------------------------=
(7mt ) (3m²t) (2mt²)

dalej musisz sam(a) bo nie ma tak wysokich poteg











2 1 2